Sustainability in the Fashion Industry: A study of fashion brands tackling social issues in the supply chain. - IBARRA MACHAIN, MIRYAM EUNICE (2017)
Fashion industry is considered the second most polluting industry in the world. Under this statement, academia and practitioners have become very interested in the aspects of environmental sustainability of the fashion supply chain but have neglected to study social dimensions. Furthermore, several scandals and tragedies related to slavery and other abuses have arisen the public attention. This work presents some of these social abuses found along the fashion supply chain and carries out an analysis of actions undertaken by fashion brands to tackle the problem. The findings were presented in 7 different areas of action. Furthermore, it was found that most of the social issues were addressed through partnerships. These partnerships were studied from different angles and informed what causes are being addressed.